Modelagem e simulação numérica de dutos enterrados sujeitos a recalque ou elevação localizados - Silva, Marcílio Fabiano Goivinho da (2012)
This work discusses general aspects of modeling and numerical simulation of a physical model using the finite element method. For this purpose, is used the commercial software Abaqus, a tool very used by the academic community, which is often used for simulation of geotechnical materials, including the study of buried pipes. The numerical model studied is a sandbox provided with a trapdoor that can move vertically. The simulations, when considering the presence of the pipe, seek to evaluate the deflections of the pipe, and when the pipe is not inserted in the model, aim the study of soil arching, considering, in both cases, moving up and down of the trapdoor. The physical model contributes providing data that supply the constitutive models, allowing comparison between the result of numerical simulations and the real behavior of the materials, permitting adjustment when necessary. The numerical models are analyzed with linear elastic and elastoplastic constitutive relations (according to the Mohr-Coulomb criteria) for the soil; and linear elastic and elastoplastic (Tresca criteria) for the pipe. The results shows that although the Mohr-Coulomb model provide better results than the linear elastic model, this elastoplastic constitutive relation does not simulate the variation of the compacity of sand, when in yielding. The model of Mohr- Coulomb includes a controlled variation of volume in the yielding in regions of massif subjected to large deformations. A linear elastic model was used in the other regions of massif. For solicitations used in the simulations, are not observed plastic deformations in the pipe.